Penggunaan Metode Active Directory Dan Privileges Pada Jaringan Komputer Untuk Penyimpanan Data Central Pada SMA Muhammadiyah 1 Bengkulu - Armansyah, Yody; Khairil; Aspriyono , Hari (Jurnal Komputer, 2023)
The use of Active Directory and Privileges Methods on Computer Networks for central data storage at SMA Muhammadiyah 1 Bengkulu is made using Samba Server, where files will be stored in folders on the server, and direct users to access the folder in order to process documents that have been stored in the folder. In the application of Active Directory, the server has installed the samba ad-dc service (Activer Directory Domain Controller) with the hostname smamuhammadiyah1.bengkulu.lan and the server IP Address 192.168.0.2 which can be accessed by each clientBased on tests carried out with server and client specifications found at SMA Muhammadiyah 1 Bengkulu, it can be concluded that the file storage process can be done well as expected, and if the file storage has a large size, then the storage process takes a long time.